The Influence of Product Quality, Perceived Price, and Brand Image on Purchasing Decisions of Nescafe Instant Coffee Powder in Surabaya - Achmad Hadi Dachlan; Ugy Soebiantoro (PT Inovasi Pratama Internasional, 2023)
This study aims to determine the effect of product quality, price perception and brand image on purchasing decisions of Nescafe instant coffee powder in Surabaya . This research method is quantitative. The population in this study is consumers who have bought and consumed Nescafe instant coffee powder products in Surabaya . The sampling technique uses non -probability sampling and uses techniques purposive sampling as a technique for determining the sample used because not all members of the sample have criteria that are in accordance with the objectives of the study . According to Hair et al., (2014: 77) the number of sample sizes that are appropriate for Partial Least Square (PLS) can be measured by the number of indicators multiplied by 5 or the sample size between 100-200 respondents. In this case the number of samples in this study is 16 (indicators) x 6 = 96 and rounded up to 100 respondents. Data collection was carried out through a Google form questionnaire to respondents with an ordinal scale via a Likert scale from a score range of 1 to 5. The data was processed using the Partial Least Square (PLS) data analysis technique. The results showed, product quality, price perception and brand image has a positive effect on purchasing decisions of Nescafe instant coffee powder in Surabaya. In conclusion, product quality, perceived price and brand image have a significant influence on purchasing decisions.